Toxicities of the copper and zinc oxide nanoparticles on Marshallagia marshalli (Nematoda: Trichostrongylidae): evidence on oxidative/nitrosative stress biomarkers, DNA damage and egg hatchability. (2nd December 2021) - Shafienejad Jalali, T.; Malekifard, F.; Esmaeilnejad, B.; Asri Rezaie, S.
Abstract: This study investigated the in vitro anthelmintic activity of copper oxide (CuO) and zinc oxide (ZnO) nanoparticles (NPs) against Marshallagia marshalli . The in vitro study was based on an egg hatch assay, adult and larvae motility inhibition assays, DNA damage, intensity protein profile along with several oxidative/nitrosative stress biomarkers including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), protein carbonylation (PCO), malondialdehyde (MDA), total antioxidant status (TAS) and nitric oxide (NO) content. Different concentrations of CuO-NPs and ZnO-NPs (1, 4, 8, 12 and 16 ppm) were used to assess anthelmintic effects on three stages of M . marshalli life cycle – that is, eggs, larvae and adult parasites for 24 h. The results indicated that CuO-NPs and ZnO-NPs played a significant role as anthelminthics, and the effect was dependent on time and concentration. The concentrations of 12 and 16 ppm of CuO-NPs and 16 ppm of ZnO-NPs resulted in the induction of oxidative/nitrosative stress (decreased SOD, GSH-Px and CAT, and increased MDA, PCO and NO), increased DNA damage, inhibition of adult and larval motility, egg hatch and low intensity of protein bands following sodium dodecyl sulphate–polyacrylamide gel electrophoresis, compared to control. It was concluded that CuO-NPs and ZnO-NPs could be utilized as novel and potential agents for the control and treatment of M . marshalli infection, and they have the pharmacological potential to be studied in vivo for further utilization in treating parasitic infections.